Analisis Manajemen Strategi Kebijakan Pembaharuan Core Tax Administration System (CTAS) dalam Upaya Penguatan Reformasi Administrasi Perpajakan di Indonesia - Rahmi, Notika; Arimbhi, Pebriana; Hidayat, Vigo Satrio (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
Tax reform is a refinement/improvement of tax administration performance carried out by the Directorate General of Taxes. One of the things that is part of tax reform is the Reform of the Core Tax Administration System (PSIAP) or Core Tax Administration System (CTAS). Currently, the DJP core system still has limitations in the form of not covering all business processes, so it is necessary to update the information technology system. This research was conducted with the aim of analyzing the strategic management of CTAS renewal policies in an effort to strengthen tax administration reform in Indonesia. The research method used is a qualitative approach and data collection techniques in the form of observation, interviews and documentation. The research results show that the strategy implementation stages have been prepared optimally but there are still things that need to be improved and perfected. Support is also available from several important aspects such as funding, leadership, organizational structure, human resources and information technology. The results of the SWOT analysis show that there are strengths in the legal basis, weaknesses in socialization, opportunities in the service process and inspections in the field and threats to the possibility of system hacking. There are inhibiting entities such as digital infrastructure that are prone to disputes and incentives in the form of preparations that are carried out according to plan. CTAS implementation will begin in 2024 and is expected to achieve the expected goals, namely ease of tax administration and strengthening of the administrative integration system.